The Tokyo 2020 Olympic Games: impacts of COVID-19 and digital transformation - Russo, E.; Roder Figueira, A.; Secches Kogut, C.; Dourado Cotta de Mello, R. (Cadernos EBAPE.BR, 2021)
The Olympic Games have been responsible for moving billions of dollars in direct and indirect investments during their winter and summer editions in the host cities they pass through, thus leaving tangible and intangible legacies that, if well used, can promote significant changes in the daily lives of societies. For the first time in the modern era of the Olympic Games, in the beginning of 2020 this cycle had to be postponed due to the COVID-19 pandemic that left more than 4 million people dead in the world by July 2021. The case puts the reader in the role of Hiroto Nakami, then President of the Tokyo 2020 Organizing Committee, to solve operational barriers and make it possible to create a successful digital Olympic Games model even behind closed doors. For this, it will be necessary to evaluate the financial and technological limitations in order to assess the impacts and legacies from these actions for the event and the local business environment. The case is suitable for multidisciplinary undergraduate and graduate students interested in discussing themes and concepts related to the area of strategic planning, crisis management, mega events, and digital transformation.